2012
DOI: 10.1111/j.1447-0756.2012.01888.x
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Prolift mesh repair in treatment of pelvic organ prolapse and its effect on lower urinary tract symptoms: 5‐year retrospective case study

Abstract: This study shows that Prolift procedure is safe and effective in women with severe pelvic organ prolapse with resolution of most of the bulge and urinary urge symptoms. Total Prolift was effective in the treatment of associated mixed urinary incontinence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 8 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…Regardless of whether the women had undergone concomitant MUS or PRS alone, low preoperative values of MUCP and FUL were significantly correlated to the high incidence of P-USI. Preoperative MUCP were noted to be lower in women who had P-SUI following Prolift T surgery in a study done by Gad et al [27]. Kawasaki and colleagues in their review concluded that low MUCP was significantly associated with higher objective failure in MUS surgery, and the preoperative value may add value to the predictive outcome of planned surgery [28].…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of whether the women had undergone concomitant MUS or PRS alone, low preoperative values of MUCP and FUL were significantly correlated to the high incidence of P-USI. Preoperative MUCP were noted to be lower in women who had P-SUI following Prolift T surgery in a study done by Gad et al [27]. Kawasaki and colleagues in their review concluded that low MUCP was significantly associated with higher objective failure in MUS surgery, and the preoperative value may add value to the predictive outcome of planned surgery [28].…”
Section: Discussionmentioning
confidence: 99%